IMPLEMENTASI WEIGHT PRODUCT (WP) UNTUK PEMILIHAN BUBUR BAYI INSTAN USIA 6BULAN+ - Linda Sari Dewi (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2020)
Instant baby porridge is one of the preferred foods for babies that are used at the age of six months and above and baby porridge or also known as solid food is a very decisive step to meet a baby's nutritional needs, the problem of fulfilling nutrition for all age groups is still not resolved at this time . The cause of malnutrition can be seen from one of the factors that are difficult to eat, the problem of difficulty eating can be seen in toddlers and this problem if not resolved quickly can affect the growth and development of toddlers due to nutritional deficiencies. Parents' desire to meet their children's nutritional needs is often in inappropriate ways, such as by promising a reward in the form of their favorite meal if the child shows good behavior, so that the child does not consume healthy food and ultimately results in bad food behavior for the child. To solve the above problems, a decision support system method is applied, namely the weighted product (WP) with the aim that parents can easily and quickly choose baby porridge food, so that there are no mistakes in meeting the nutritional needs of their children. The results obtained in the calculation of the Weighted Product Method which consists of several calculation stages, starting from determining alternatives and criteria, baby porridge selection criteria, weight importance level, criteria weighting, vector calculation to ranking are products for selecting baby porridge, there are 2 best alternatives, namely A11 with a value of 0.09390 and A12 with a value of 0.09390.Keywords: weight product, instant baby porridge Bubur bayi instan salah satu makanan pilihan bayi yang digunakanan pada usia enam bulan keatas dan bubur bayi atau juga disebut dengan makanan padat merupakan langkah yang sangat menentukan untuk memenuhi suatu kebutuhan gizi bayi, permasalahan pemenuhan gizi dari seluruh kelompok umur masih belum bisa diselesaikan pada saat ini. Menyebabkan gizi yang kurang dapat dilihat dari salah satu faktor sulit makan, masalah sulit makan dapat dilihat pada balita dan masalah tersebut jika tidak diselesaikan dengan cepat dapat mempengaruhi pertumbuhan dan perkembangan balita dikarenakan kekurangan nutrisi. Keinginan para orang tua untuk memenuhi kebutuhan nutrisi anaknnya sering kali dalam pemberian makanan dengan cara yang kurang tepat seperti dengan menjanjikan hadiah  berupa makan kesukaannya jika anak menunjukkan perilaku yang baik, sehingga anak tidak mengkonsumsi makanan sehat dan akhirnya mengakibatkan perilaku makanan yang tidak baik bagi anak. Untuk menyelesaikan permasalahan diatas, maka diterapkan metode sistem penunjang keputusan yaitu weighted product (WP) dengan tujuan agar para orang tua dengan mudah dan cepat dalam memilih makanan bubur bayi, sehingga tidak tejadi kesalahan dalam memenuhi kebutuhan gizi anaknya. Adapun hasil yang diperoleh dalam perhitungan Metode Weighted Product yang terdiri dari beberapa tahap perhitungan, mulai dari penentuan alternatif dan kriteria, kriteria seleksi bubur bayi, kingkat kepentingan bobot, pembobotan kriteria, perhitungan vektor hingga perangkingan adalah produk untuk penyeleksian bubur bayi didapatkan 2 alternatif  terbaik  yaitu A11 dengan nilai 0,09390 dan A12 dengan nilai 0,09390.Kata kunci: weight product, bubur bayi instan